2009
DOI: 10.1111/j.1365-2958.2009.06618.x
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular stabilization and activity augmentation of enterohaemorrhagic Escherichia coli haemolysin

Abstract: SummaryHaemolysin from enterohaemorrhagic Escherichia coli (EHEC-Hly), a putative EHEC virulence factor, belongs to the RTX (repeat-in-toxin) family whose members rapidly inactivate themselves by selfaggregation. By investigating the status of EHEC-Hly secreted extracellularly, we found the toxin both in a free, soluble form and associated, with high tendency and independently of its acylation status, to outer membrane vesicles (OMVs) extruded by EHEC. We compared the interaction of both toxin forms with eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 54 publications
(90 reference statements)
5
64
0
Order By: Relevance
“…The isolation of STEC O91 strains from stool samples positive in the screening procedures using SMAC and CT-SMAC (commonly used for the isolation of E. coli O157:H7) (44) is hindered by the ability of the vast majority of such strains to ferment sorbitol and by their tellurite susceptibility. However, most (73.0%) STEC O91 isolates produced EHEC hemolysin, a potent cytolysin of red blood cells (1), and expressed an enterohemolytic phenotype on enterohemolysin agar, which distinguishes these strains from E. coli found in physiological intestinal flora. Therefore, enterohemolysin agar can be used for isolation of many STEC O91 strains from stx/Stx-positive primary stool cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of STEC O91 strains from stool samples positive in the screening procedures using SMAC and CT-SMAC (commonly used for the isolation of E. coli O157:H7) (44) is hindered by the ability of the vast majority of such strains to ferment sorbitol and by their tellurite susceptibility. However, most (73.0%) STEC O91 isolates produced EHEC hemolysin, a potent cytolysin of red blood cells (1), and expressed an enterohemolytic phenotype on enterohemolysin agar, which distinguishes these strains from E. coli found in physiological intestinal flora. Therefore, enterohemolysin agar can be used for isolation of many STEC O91 strains from stx/Stx-positive primary stool cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of Ehx in virulence has been unclear, several investigations have led to some insight on its contribution to disease. These toxins have been shown to be associated as cargo with outer membrane vesicles (OMVs), prolonging its activity (287). Additionally, Ehx was found to be cytotoxic to endothelial cells and may contribute to the development of HUS (288).…”
Section: Pathogenesismentioning
confidence: 99%
“…When in similar experiments the lungs were primed by preexposure to LPS, the effects of HlyA on thromboxane release and blood pressure were 15-fold more severe than those without priming, indicating that the response to LPS, the release of TNF-␣ into the medium, synergizes with the effects of HlyA (418). In vitro studies showed that HlyA may be associated with E. coli outer membrane vesicles (OMVs), which may also contain additional bacterial factors, suggesting that such vesicles may alter cellular responses (419).…”
Section: Other Effects Of Pfts On the Vasculaturementioning
confidence: 99%